Caracterização de tráfego entre filas M/ G/ c/ c dependentes de estado - Harley Francisco de Araujo (2004)
This dissertation deals with issues related to modeling inter-queue traffic in network of M/G/c/c state-dependent queues. We considered queues in series, merges, and splits. In order to evaluate the systems, we observed mainly the inter-departure time, but also regarded were the traditional performance measurements such as blocking probability, throughput, work-in-process, and sojourn time. Our results point to a good fit of the exponential distributions in modeling the inter-queue inter-departure time, in almost all cases tested.